THE NEED FOR IMPLEMENTATION OF ISLAMIC SOCIO ACCOUNTING - Bayu Eka Silvia (Indonesian Management and Accounting Research, 2007)
Conventional Accounting is argued to be unsuitable for an Islamic Society because it embraces fundamental values and principles which are in conflict with its value. Adopting or even modifying conventional Accounting concept is insufficient to develop an accounting system which provides information that will lead to behavior consistent with Islamic norms and towards Islamic objective. Besides, Conventional accounting has increasingly come under attack in its home ground because of it adopting a narrow marginalist, utilitarian economic principle and the assumption of a pristine liberal economics democracy as the basis of soc iety. This paper aimed to emphasized how important is the implementation of Islamic Socio accounting in Islamic Economics and Islamic Financial institution, by showing critics on conventional accounting, its philosophy under value and inability of Conventional Accounting to be applied in Islamic Economics, particularly at their incapability for the purpose of Zakat and interest-free banking.JEL Classification:Keywords: Conventional Accounting, Islamic Socio accounting, Zakat , Islamic Banking